The Future of Press Freedom (Cambridge University Press, 2026)
This volume explores how law and policy can protect press freedom in a changing news landscape. It offers journalists, lawyers, policymakers, and concerned citizens expert insights into how to safeguard journalism through innovative governance. Readers will gain a crucial understanding of how to preserve this pillar of American democracy.